Structure, magnetism and catecholase activity of the first dicopper(ii) complex having a single μ-alkoxo bridge1. Issue 15 (25th February 2015) - Adhikari, Sangita; Banerjee, Arnab; Nandi, Sandip; Fondo, Matilde; Sanmartín-Matalobos, Jesús; Das, Debasis
<x xml:space="preserve">Abstract</x> Pyridine-2, 6-dimethanol shows a neutral, monoanionic and dianionic coordination behaviour with two different coordination modes viz. tridentate and bidentate towards Cu(ii), leading to three different geometric environments around Cu(ii) centers.